DETERMINANTS OF AUDITING ELECTRONIC ACCOUNTING INFORMATION SYSTEMS, A CASE STUDY IN THE JORDANIAN COMMERCIAL BANKS - Al-Bashtawi, Suliman Hussein; Al-Husban, Atallah (European Scientific Journal, ESJ, 2013)
The study has clarified the determinants faced by the external auditor during the process of auditing different electronic accounting information systems, at which the study included units, IT departments, administration, finance and accounting departments in banks operating in Jordan, which are (19) Banks, which represented the community and the sample of the study; the study has considered the views of a group of managers, employees and workers in the units of information security or accounting business in general. From the analysis of the results of the practical side and the use of the statistical program SPSS, the study has shown the presence of problems and obstacles that the auditor faces, which restrict the required procedures of auditing before auditing the computerized accounting information systems, such as determining the possibility of dealing with the main issues, like conditions of uncertainty, how to determine those conditions and what to do in case they occur, because of the seriousness and their threat as a result of the likelihood of recurrence of the event (incidence of threat). The study has recommended a set of recommendations, the most important are: increasing auditing procedures required to assess old computers, trying to determine the feasibility of using them in computerized information systems, as well as determining the value of the data or information itself depending on the predetermination of the level of sensitivity of the information of the company, with the need for the auditor to prepare a preliminary report on risks of control to make sure of the financial accounts or set of operations and risks of various types of auditing, as well as try to reduce them as much as possible.